ANALYSIS OF PLTMH POTENTIAL USING CASIMIR HYDROPOWER APPLICATION AT SALOMEKKO DAM - Nurul Ulfa; Zulhajji, Zulhajji; Firdaus, Firdaus; Haripuddin, Haripuddin; Yantahin, Muliaty (Jurusan Pendidikan Teknik Elektro, 2025)
This research aimed to: 1) determine the water discharge and head (fall height) at the Salomekko Dam; 2) assess the potential electrical power that can be generated by the micro-hydro power plant (PLTMH) at the Salomekko Dam; 3) identify the type of turbine suitable for the PLTMH based on the water discharge and head (fall height) at the Salomekko Dam in Salomekko District, Bone Regency. The data collection techniques applied are observation, documentation, and interviews. The data analysis techniques used was theoretical power potential calculations by using the Hydropower Casimir software, based on data from relevant agencies, the central statistics agency, and dam management. The results of this study were: 1) the water discharge per year: Q2021 = 16.623 m³/second, Q2022 = 17.787 m³/second, Q2023 = 18.199 m³/second, H = 13.83 meters; 2) the potential electrical power that can be generated by the Salomekko Dam's PLTMH: P2021 = 1804,22 kW, P2022 = 1930,56 kW, P2023 = 1975,28 kW; 3) the Kaplan turbine was the type of water turbine used for power generation at the Salomekko Dam in Salomekko District, Bone Regency, based on the water discharge and head.